Transient receptor potential channels as key regulators of cell death in atherosclerosis - Zhang, Yibo; Wang, Weiguo; Li, Xuemin; Li, Xuewen; Zheng, Lei (Frontiers in Immunology, 2025)
Transient receptor potential (TRP) channels are non-selective cation channels with diverse physiological functions, widely expressed across various cell types. These channels play crucial roles in maintaining homeostasis and contribute to the progression of cardiovascular diseases, particularly atherosclerosis. Atherosclerosis is a chronic vascular inflammatory condition marked by lipid accumulation and fibrous tissue proliferation in the arterial intima. TRP channels regulate intracellular ionic gradients and activate downstream signaling pathways, thereby influencing the function of vascular endothelial and smooth muscle cells. Therefore, they are increasingly implicated in the pathogenesis of cardiovascular and cerebrovascular diseases. Emerging evidence has demonstrated that pharmacological modulation (antagonism or activation) of TRP channels regulates programmed cell death mechanisms, positioning these channels as key modulators of atherosclerotic plaque dynamics. Specifically, TRP channels modulate various cell death modalities, including apoptosis, autophagy, and necrosis, while also influencing inflammatory responses and oxidative stress-related pathways that potentiate cellular death. These interconnected mechanisms significantly contribute to the development of atherosclerotic lesions. This review systematically examined the mechanistic roles of TRP channels in atherosclerosis via regulation of cell death pathways, aiming to provide a comprehensive understanding of their pathophysiological functions and to support the development of targeted molecular therapies.